Preferensi Pembiayaan Qardhul Hasan di BMT Sampang Indonesia - Santika, Mela; Dzikrulloh, Dzikrulloh (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This research aims to analyze the influence of promotion, knowledge and perception on public interest. The population in this study was BMT Sampang. The sampling technique used the purposive sampling method which resulted in 46 customers. Data was collected using primary data from customers registered at BMT Sampang. The data analysis method uses logistic regression analysis. The results of this research show that the promotion variable and perception variable have a negative effect on public interest, while the knowledge variable has a positive effect on public interest. Keywords: Public Intrest; Qardhul Hasan; BMT Sampang